PENGARUH BUDAYA ORGANISASI TERHADAP PERILAKU IHSAN PERAWAT MELALUI PERSONAL VALUES PADA RUMAH SAKIT ISLAM GONDANGLEGI MALANG - Hilmi, Moh Adi; Nurdiana, Ilfi (IQTISHODUNA, 2017)
Abstract: Every organization must have a culture that guides the organization. Someone will work seriously ifin a comfortable atmosphere and working environment. The purpose of this study was to find out how big inthe organizational culture directly or indirectly that influenced the Nurses Ihsan Behavior at GondanglegiIslamic Hospital of Malang. Type of research used a quantitative research model with descriptive or surveyapproach that aimed at testing the predefined hypothesis. The object of this study was conducted atGondanglegi Islamic Hospital of Malang. The sample used 72 respondents with non-probability samplingtechnique. The result indicated that the organizational Culture had direct and significant effect to NursesIhsan Behavior. The Organizational Culture had significant effect to Ihsan Behavior through Personal Values.It meant that if in the organizational culture and personal values increase, then the Nurses Ihsan Behavior willalso increase variable.